Research of the problems of project financing of construction of residential real estate using the escrow account mechanism - I. A. Pantyukov; V. A. Opekunov (Вестник университета)
The article shows the current situation in the real estate market. The publication considers the main problems of financing investment and construction projects, as well as the use of the escrow account mechanism. The study also proposes the main ways to solve the existing issues. The main focus of the research paper is on the lack of explanations regarding the ability of banks to dispose of money in escrow accounts, credit conditions, as well as the growth in real estate prices when developers switch to a new mechanism of settlement with shareholders. In addition, the authors analysed the pricing policy of developers before and after amendments to Federal Law No. 214-FZ, dated on December 30, 2004 “On Participation in Shared-Equity Construction of Apartment Buildings and Other Real Estate Objects and on Amendments to Certain Legislative Acts of the Russian Federation”. The study presents the possible consequences of introducing amendments to the law, switching to escrow accounts.